2022
DOI: 10.1159/000523951
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Accuracy of Two Different Criteria for the Detection of Caries Lesions around Restorations in Primary Teeth

Abstract: This is a delayed-type cross-sectional prospective accuracy study nested in a randomized clinical trial. The aim was to investigate the diagnostic accuracy of two visual criteria for caries lesions detection around restorations in primary teeth: the International Dental Federation (FDI) criteria, considering adaptation, staining and presence of caries, and the Caries Associated with Restorations and Sealants (CARS) system. For this, one examiner made the diagnosis and subsequent treatment decision using visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As outlined, marginal staining, typically noted for anterior restorations in the esthetic domain, was integrated here to examine its potential as a caries predictor. The latest FDI version cautions against equating marginal staining with secondary caries, aligning with the existing literature (Mjör and Toffenetti 2000;Moro et al 2022;Uehara et al 2023). The updated criteria highlight the importance of considering marginal adaptation scores in conjunction with lesion location and the patient's caries history, risk, and activity when determining the treatment decision.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As outlined, marginal staining, typically noted for anterior restorations in the esthetic domain, was integrated here to examine its potential as a caries predictor. The latest FDI version cautions against equating marginal staining with secondary caries, aligning with the existing literature (Mjör and Toffenetti 2000;Moro et al 2022;Uehara et al 2023). The updated criteria highlight the importance of considering marginal adaptation scores in conjunction with lesion location and the patient's caries history, risk, and activity when determining the treatment decision.…”
Section: Discussionmentioning
confidence: 91%
“…If so, primary caries diagnostic criteria should apply, focusing on lesion extension and activity for treatment (Dennison and Sarrett 2012). Results derived from this trial indicated that overemphasis on marginal defects might lead to false positives and overtreatment (Uehara et al 2023), a trend also seen in primary teeth (Moro et al 2022).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the CARS system evaluates only the same stages as coronal primary caries and does not present any treatment decision linked to the evaluation method. However, the authors of the present study adapted the decisions based on the recommendations for the treatment of primary caries lesions and has been using on studies to investigate secondary caries in primary teeth [Moro et al, 2020a;Moro et al, 2020b;Moro et al, 2022]. Nevertheless, there is a lack of evidence about the accuracy and impact of both criteria on caries around restoration assessment in permanent teeth.…”
Section: Introductionmentioning
confidence: 99%